EVALUASI PROGRAM EKSTRAKURIKULER PRAMUKA DENGAN MODEL KIRKPATRICK DI SMP IT YASHODA BOGOR - Aldya Framesti; Sukma Ayu Lestari; Tita Hasanah (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2026)
This study aims to evaluate the Scout extracurricular program at SMP IT Yashoda Tenjolaya, Bogor Regency. The subjects of the study included the principal, Scout trainer, student affairs department, and students. The research approach was qualitative using the Kirkpatrick evaluation model which consists of four stages, namely reaction evaluation, learning evaluation, behavior evaluation and outcome evaluation. Data collection techniques were by filling out satisfaction sheets, observation, interviews, and documentation. The stages of data analysis include information collection, information reduction, drawing conclusions, and presenting information. The evaluation results showed that the Scout extracurricular program at SMP IT Yashoda was included in the good category and was recommended to be continued by improving its quality. It is hoped that the results of this evaluation study will be constructive input for SMP IT Yashoda.